(untitled) (Al-Academy, 2017)
This research to study the effectiveness of the reception in the interactive theatre revealed the impact of this receipt in the educational process, and has focused on regarding the role of interactive theatre in education, the role of the interactive receiver, and how this type of theater that have an impact on the process of learning and education aimed at the receiver positive actor, this research was to examine this in detail through theatrical prepared for this purpose with a group of students (fine arts Institute for girls/morning), and marking research under Address (effectively receive interactive theatre) as taken from the theme Finder receive education through theatre material for consideration, as follows: 1. Chapter I (methodological framework) which includes: problem and needed, the importance of research and research, and the temporal and spatial boundaries, and determine terms 2 2. Chapter II: conceptual framework and consists of two sections: first section: effectively receive the learning process. section II: interactive theatre: and then put the researcher most indicators that emerged from theoretical framework. 3. Chapter III-procedures:-search community: 4 chapter IV: findings and conclusions (conclusions, findings, proposals, recommendations, bibliography, references, appendices, abstract in English.